Pengembangan Mobile Learning Management System Berbasis Blended Learning pada Pembelajaran Masa WFH Pandemic Covid-19 - Rony Wijanarko; Moch Abu Choir (Universitas Wahid Hasyim, 2023)
The spread of the Coronavirus (Covid-19) outbreak, which has spread so quickly throughout the world, has caused anxiety and sadness for humanity to grieve. Starting from Wuhan China since the end of January 2020. The World Health Organization (WHO) has determined the phenomenon of this incident as a pandemic. A pademic occurs when an infectious disease spreads easily from human to human in various places in all corners of the world. Until the last two weeks, cases of Covid-19 outside China have increased thirteen times, causing concern for the world community. This research tries to provide solutions to the problem of how to develop and access LMS for learning anywhere and anytime (ubiquitos learning) both online and offline, using mobile devices that have limited connections. The M-LMS application being developed will be in the form of a prototype that takes the open source Moodle LMS model, and will focus on only a few important modules, namely the Subject Description module, Assignment module, Quiz module, Subject matter module. In its implementation, this research will be divided into three stages, namely pre-development data collection, development and implementation, and post-development data collection. The pre-development data collection is intended to obtain provision for a preliminary study of the core problems being faced, while the development and implementation stages focus on modeling software designs into diagrams and creating programming code to implement the designs that have been made. While the post-development data collection stages are for improving the applications made, drawing conclusions, and suggestions for further research topics.